Estilos de aprendizaje de los estudiantes de sexto grado en una institución educativa pública y privada del Callao - Leiva Torres, Jakline Gicela (2012)
The aim of this research was to determine the learning styles of sixth grade primary school students from a public school students and those who belong to a private school in Callao Region. This was a descriptive research and the design is descriptive comparative : There are 178 students participatedin this research 90 from a public school and 88 from a private school The V.A.K performed by Ralph and adapted by Leiva was used to this research. The results show that there are no significant differences between both schools.